Exploring the Practices of Refugee Settlement Practitioners in Toronto: An Institutional Ethnography. Issue 4 (2nd October 2021) - Parada, Henry; Limón Bravo, Fabiola; Loewen, Rebecca; El-Lahib, Yahya
Abstract: Using Institutional Ethnography as a method of inquiry, this study explores the institutional ruling relations that regulate refugees' settlement process in Toronto from the standpoint view of practitioners. The research team conducted 13 semi-structured, in-depth interviews with practitioners and "mapped out" their everyday living experiences. The institutional map serves to illuminate how governance structures shape the professional practices of practitioners, which shape the settlement experience of refugees. The findings indicate that practitioners strategize to meet refugees' needs and engage in work outside of the system due to funding constraints.